OUR EXPERIENCE WITH SURGICAL TREATMENT OF ROTATOR CUFF INJURIES OF THE SHOULDER JOINT - Temurov A.A., Khursanov M.Kh., Nurumov S.Y. (Central Asian Journal of Medicine, 2025)
CSJ injuries occur in 63-84% of shoulder injuries. The rotator cuff ranks third (16%) after spinal (23%) and knee (19%) disorders in terms of frequency of rotator cuff injuries. The frequency of tears varies from 5 to 37% (A. DePalma), of which about 15-20% in 60-year-olds, 26-30% in 70-year-olds, and 36-80% in 80-year-olds. Such a high incidence of pathology is predetermined by regular degenerative changes in the tendinous and muscular tissues of the rotator cuff of the shoulder, which develop in people with age and are caused by anatomical features of the shoulder joint structure. In the tendon part of the rotator cuff of the shoulder there is a so-called ‘load cable’ or ‘sickle-shaped area’, within which blood flow is reduced, and there the tear formation occurs. Magnetic resonance imaging (MRI) is highly informative in the diagnosis of pathological changes of the rotator cuff of the shoulder. T2-VI with signal suppression from fatty tissue in the oblique coronal projection is considered to be the most informative.